Liquid futures: Water management systems and anticipated environments. (9th January 2018) - Randle, Sayd; Barnes, Jessica
Abstract : Climate change and its impact on hydrological dynamics have become key topics of concern among water managers and policy makers in many parts of the world. Yet while practitioners often frame adaptation to a climate‐changed future as a novel issue, ideas about future environments have long influenced systems of water management. Reviewing ethnographic and historical accounts of waterscapes across the globe, this article examines the relationship between imagined environmental futures and the policies, practices, infrastructures of water management and legal frameworks. We show, first, how conflicting ideas about environmental stasis and perturbation have been built into water networks across space and time. In some cases, notions of radical landscape change have underpinned these systems, as in programs dedicated to land "reclamation" or interbasin water transfer schemes. In other contexts, water systems have developed based on visions of long‐term sociohydrological stability. Second, we highlight how contrasting notions of human capacity to change environmental outcomes have played into water management systems. In some cases, there has been an assumption of the potential for and desirability of full human control; in others, there has been more recognition of the limits of such mastery. Exploring the wide range of environmental imaginaries mobilized through water management, we contextualize contemporary efforts to build resilient, "climate proof" waterscapes. WIREs Water 2018, 5:e1274. doi: 10.1002/wat2.1274 This article is categorized under: Human Water > Water as Imagined and Represented Science of Water > Water Quality Abstract : A dried reservoir bed, emblematic of concerns about water scarcity and one of many anticipated environmental futures that shape water management systems across the globe. (Photo by Sayd Randle).